Domestic Investment, GDP and Inflation: Their Impact on Extreme Poverty in Indonesia - Fitria Nur Aini; Sutrisno; Moh Mustofa (Universitas Indo Global Mandiri, 2025)
This research aims to analyze how domestic investment, gross domestic product and inflation influence extreme poverty in Indonesia during the 2004-2024 period. In the future, it is hoped that this research can become the basis for further research on comprehensive economic policies that focus on increasing domestic investment and GDP as well as controlling inflation to reduce extreme poverty in a sustainable manner. Secondary data sources were obtained through BPS and Word bank, using a quantitative approach and multiple linear regression analysis with the help of data processing through the EViews 13 program. It was found that the research results showed that domestic investment had an effect but was not significant, while GDP and inflation had a significant effect on extreme poverty in Indonesia. This study finds that growth in domestic investment and GDP has an influence in reducing extreme poverty by increasing people's purchasing power and income. Inflation, on the other hand, exacerbates extreme poverty by suppressing the purchasing power of vulnerable groups. This emphasizes the importance of increasing domestic investment, inclusive economic growth and controlling inflation.These findings highlight the need for policies that maintain stable PMDN growth, encourage inclusive economic growth, and control inflation to effectively reduce extreme poverty in Indonesia. The implications of this research suggest that the government needs to integrate economic strategies that focus on stability and controlling inflation in poverty alleviation policies, especially to improve the welfare of low-income groups. Keywords: Domestic Investment; Gross domestic product; Inflation; Extreme Poverty